VD_FINDINFO Décision / 2012 / 942 vom 7. August 2012 - VD Tribunal cantonal (2012)
ADMINISTRATION DES PREUVES, POLICE, MINISTÈRE PUBLIC, OUVERTURE DE LA PROCÉDURE | 309 al. 2 CPP (CH), 310 CPP (CH), 393 al. 1 let. a CPP (CH)